1978
DOI: 10.1007/bf00253116
|View full text |Cite
|
Sign up to set email alerts
|

High volume intraperitoneal chemotherapy (?Belly bath?) for ovarian cancer

Abstract: The currently accepted therapies for ovarian cancer have produced only limited numbers of extended complete remissions in advanced-stage disease. Studies of high-volume intraperitoneal chemotherapy have been initiated to define the toxicology, pharmacokinetics, and the therapeutic effectiveness of this treatment modality. This technique has been virtually ignored until recently, because little success has been achieved with it except in one study (Rutledge, 1966), in which large intraperitoneal fluid volumes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
7

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(42 citation statements)
references
References 15 publications
2
33
0
7
Order By: Relevance
“…Dedrick studied the pharmacokinetics of IPC and found that hydrophilic cytotoxic drugs can maintain a significant concentration gradient along the peritoneal plasma barrier; with high intraperitoneal concentrations when added in the abdominal cavity in large volumes [33], however is limited by the restrictive penetration depth in tumour tissue of approximately 1-3 mm. He stated that the peritoneal clearance of the drug is inversely proportional to the square root of its molecular weight [34] and stated the peritoneal permeability to a certain drug is lower than the same drug's plasma clearance [35].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Dedrick studied the pharmacokinetics of IPC and found that hydrophilic cytotoxic drugs can maintain a significant concentration gradient along the peritoneal plasma barrier; with high intraperitoneal concentrations when added in the abdominal cavity in large volumes [33], however is limited by the restrictive penetration depth in tumour tissue of approximately 1-3 mm. He stated that the peritoneal clearance of the drug is inversely proportional to the square root of its molecular weight [34] and stated the peritoneal permeability to a certain drug is lower than the same drug's plasma clearance [35].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The most common example of this is the successful treatment of meningeal leukemia with intrathecal MTX (13)(14)(15). Pharmacologic modelling (16) suggested that the clearance of MTX from the peritoneal cavity would also be sufficiently less than total body clearance to allow significant differential exposure for tumor cells in the peritoneal cavity, and recent studies of MTX administered via peritoneal dialysis confirmed that at steady state the peritoneal concentration of MTX was 10-to 30-fold higher than in plasma (17). However, at peritoneal MTX concentrations high enough to guarantee good drug penetration, enough MTX leaked into the systemic circulation to be toxic to marrow, and the duration of peritoneal dialysis had to be limited to 48 h.…”
Section: Introductionmentioning
confidence: 99%
“…22 Average sizes of these liposomes were about 180 -200 nm and there were no significant differences in average size between bare liposomes, PEG liposomes and Tf liposomes. If necessary, 3 H-CHE was added as a membrane marker. …”
Section: Liposome Preparationmentioning
confidence: 99%
“…There have been few reports of effective treatment for peritoneal dissemination in patients with gastric cancer. 2,3 As a clinical locoregional chemotherapy, various anticancer drugs in solution form have been administered i.p. to expose the drug directly to peritoneal tumor cells.…”
mentioning
confidence: 99%